Tatianna Raspotnik: capstone - Raspotnik, Tatianna, artist and filmmaker (Colorado State University. Libraries, 2018)
The artist's statement: I focus on the interaction between the physical and digital worlds since they intertwine more than they ever have before, especially in popular culture. Creating artwork that can live in both a gallery as well as online is interesting to me. Both lives are different, but not separate. For the last four years, I've been exploring the duality of digital art and how viewers interact with it in different settings. One way to explore the work in its multiple lives is to present it in multiple different states and then observe the different interactions within. For example, I find that an interactive experience is enjoyed most when directly participating in it. However, when it is observed through video and still image, its message and meaning completely change. So when creating art pieces, I consider these differences in the experiences by using multidimensional thinking and consideration.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
Security blanket has no audio. Visual musical score, Flip book flowers, and Outlook: interactive experience have no spoken word.
Keywords: electronic art